Care and temporality: pediatric nursing in the Joint Permanence System of a teaching hospital - Helena Becker Issi; Maria da Graça Corso da Motta (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To understand, in the temporality, the care phenomenon of the child and family in the scope of Pediatric Nursing of a teaching hospital. Method: This is a phenomenological and hermeneutical study which uses the existential focus of Martin Heidegger and Ricoeur`s hermeneutical analysis. Interviews were carried out with nine nurses of the Pediatric ward of the Porto Alegre's Clinical Hospital and with a teacher of the Nursing School of the Federal University of Rio Grande do Sul involved in the implementation of Pediatrics, between December 2014 and June 2015. Results: In the temporality of Pediatric Nursing, the care model has been designed as a Joint Permanence System. The following dimensions have been revealed: creation process, care proposal, teaching, evolution in the development of time. Conclusions: Pediatric Nursing introduces a pioneer care model that guarantees and qualifies the presence of the family next to the hospitalized child. It reaffirms the originality, topicality and innovation of this knowledge and the way of performing the care actions. It may be disseminated and replicated in other contexts of care, teaching and research.